PENANGANAN GANGGUAN LISTRIK RUMAH TANGGA MENGGUNAKAN ALGORITMA GREEDY UNTUK PENENTUAN JARAK OPTIMAL - Ayu Fadhilah Prianty; Riki Ruli A. Siregar; Rakhmat Arianto (JURNAL TEKNOLOGIA, 2019)
Electricity is a necessity that can be said has become the basic needs of society today. By exploiting technological developments, it is expected to facilitate PLN electricity customers in reporting electrical disturbances easily so that officers can provide response handling disorders quickly. One of the most commonly utilized technologies is Internet technology that can easily access website applications. Technical Service Post, PLN Area Cengkareng and Kalideres not utilize it well, for that need an application that can do the calculation of the optimal distance from report point to nearest duty using Greedy Algorithm. In the optimization problem, the Greedy Algorithm can produce an optimal solution. With the process, customers can easily find the nearest PLN officers, monitor the status of the report so that expected information can be immediately responded to disruption and handling